A COMPARATIVE STUDY OF HAEMODYNAMIC EFFECTS OF INTRATHECAL VERSUS INTRAVENOUS FENTANYL FOR SUPPLEMENTATION OF SUBARACHNOID BLOCK IN PATIENTS UNDERGOING TOTAL ABDOMINAL HYSTERECTOMY - Dr. Ashiq Kalam; Dr. Harini Priyadarshini M. S; Dr. Priyanka N. Maiya; Dr. Shivashankar M (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
BACKGROUND: Although there are studies comparing various opioids and various dosages of fentanyl, studies comparing the two routes of administration with respect to their haemodynamic effects, especially for total abdominal hysterectomy are very few. METHODS: Inj. fentanyl 25µg (0.25 ml) intrathecally and Inj. fentanyl 1µg/kg intravenously were compared. 15 mg of 0.5% hyperbaric Bupivacaine was used for spinal anaesthesia in both groups. Vital parameters, including heart rate, SBP, DBP, MAP, and SpO2, were measured at baseline and at intervals of 5 minutes for 30 minutes, followed by every 15 minutes till 120 minutes. Hypotension was defined as a reduction in SBP (Systolic Blood Pressure) of more than 30% below the baseline or a fall in SBP less than 90 mmHg. It was treated with increasing the rate of intravenous fluid administration and inj. mephenteramine 3mg IV in incremental doses, if required. Bradycardia was defined as a heart rate less than 30% of the baseline heart rate. It was treated by inj. atropine 0.6 mg IV. RESULTS: The heart rate and SpO2 values at timed intervals in both groups were comparable. Between the two groups, no statistically significant variations in heart rates or SpO2 were observed. When the SBP at timed intervals was evaluated between the two groups, it was discovered that there was a statistically significant difference in the mean SBP just after the subarachnoid block and five minutes later, with the IT fentanyl group seeing a larger drop in blood pressure. IV fluids and a injection of mephenteramine 3mg were used right away to rectify it. Other time intervals showed comparable mean SBP. Clinically, the IT fentanyl group had a lower mean SBP than the IV fentanyl group. When the two groups’ DBP was evaluated at timed intervals, it was discovered that there was a statistically significant difference in the mean DBP at 30 and 45 minutes, with the IT fentanyl group seeing a larger drop in blood pressure. IV fluids and a 3mg injection of mephenteramine were used right away to rectify it. Other time periods had similar mean DBP. Clinically, the IT fentanyl group had a lower mean DBP than the IV fentanyl group. When the two groups’ MAP at timed intervals were examined, it was shown that there was a statistically significant difference in mean MAP at 30 and 45 minutes, with the IT fentanyl group seeing a larger drop in blood pressure. IV fluids and a 3mg injection of mephenteramine were used right away to rectify it. At other intervals, the mean MAP was similar. Clinically, the IT fentanyl group had a lower mean MAP than the IV fentanyl group. CONCLUSION: Although comparatively lower Systolic Blood Pressure, Diastolic Blood Pressure & Mean Arterial Pressure were observed with intrathecal administration, the incidence of hypotension (SBP<90 mmHg) was higher with intravenous fentanyl. Intrathecal administration of fentanyl provides longer duration of sensory and motor block and better postoperative analgesia when compared to intravenous fentanyl.